Karakterisasi Sifat-Sifat Arang Kompos dari Limbah Padat Kelapa Sawit (Elaeis guinensis Jack) Characterization of Compost Charcoals Properties from Oil Palm Solid Waste - Erlidawati Erlidawati; Abdul G Haji; M. Nasir Mara; Asri Gani; Sarwo Edi; Diana I Sari (Jurnal Ilmu dan Teknologi Kayu Tropis, 2009)
Oil palm solid waste especially fruit and empty bunches are hard to decompose naturally in the environment because fruit bark still contains oil and empty bunches contain cellulose, hemicelluloses and lignin with relatively similar levels. In this research, the quality of compost charcoals from raw materials of oil palm solid waste was studied.Oil palm empty bunches were pyrolized in a drum reactor at optimum temperature. Charcoals were milled and mixed with oil palm fruit bark to make compost charcoals by using biodecomposer Dobura1 and EM-4. Compost charcoals were characterized and their qualities were compared with the organic waste compost in accordance with SNI-19-7030-2004.The production of compost charcoals in all treatments in this research indicated that the fluctuating temperatures were changes especially in the first day and in the second day until the fourth day, decreased gradually and then rose again slowly. pH values in all treatments showed a very sharp increase in the first day, except for control that were rose up to the second day, whereas in the third day they all showed a rather sharp decrease, then in the fourth day and forth rose again slowly. The weight shrinkage of compost charcoals in all treatments occurred significantly until the sixty day. Compost charcoals that were produced in all composting treatments fulfilled the compost quality of domestic waste in accordance with SNI-19-7030-2004.